Rational design of a 3D MoS2/dual-channel graphene framework hybrid as a free-standing electrode for enhanced lithium storage. Issue 28 (29th June 2018) - Wang, Wenxu; Yang, Puheng; Jian, Zhixu; Li, Honglei; Xing, Yalan; Zhang, Shichao
Abstract : The unique 3D dual-channel graphene framework could improve electron transport by GF channels possessing high electrical conductivity and facilitate Li ion diffusion by GA channels shortening the diffusion pathways. Abstract : Integrating high-capacity MoS2 with carbon materials, especially graphene, into a rationally designed structure has been demonstrated an effective strategy to construct anode materials with superior electrochemical performance for application in lithium ion batteries (LIBs). Here, a rationally designed 3D MoS2 /dual-channel graphene framework (MoS2 /GA–GF) hybrid has been constructed through a two-step method. This dual-channel graphene framework (GA–GF) consists of two types of channels with different graphene types, graphene foam channels improving electron transport and graphene aerogel channels facilitating Li ion diffusion. With this structure, the MoS2 /GA–GF hybrid can efficiently improve electron and Li ion transport kinetics and accommodate the MoS2 volume change during cycling. Benefiting from the above merits, the MoS2 /GA–GF electrode as a free-standing electrode presents a high initial capacity (1404 mA h g −1 ) with a high initial coulombic efficiency (81.7%), excellent rate capability (593 mA h g −1 at 5 A g −1 ) and a superior long-term cycling stability (843 mA h g −1 at 1 A g −1 after 500 cycles) when evaluated as an LIB anode. Therefore, the GA–GF as a support and current collector is expected to be ideal for application in LIBs and other electrochemical energy storage devices.